IDEOM vitiligo work group: an update on our first year. (18th January 2023) - Silverberg, Nanette B; Cohen, Arnon; Desai, Seemal; Francis, Priyanka; Francis, Vimala; Gardner, Jackie; Guarino, Carrie; Guarino, Isabella; Huang, Victor; Rosmarin, David; ,
Abstract: The new Vitiligo Work Group of IDEOM was created in October 2021 and met at the annual IDEOM meetings of 2021 and 2022. The mission of the workgroup is to develop core outcome measures in vitiligo that meet three criteria: to meet the needs of stakeholders of all types, to be validated for clinical trials and studies, and to be used in all age groups of patients. The Vitiligo Work Group met November 2021 and June 2022, yielding a list of 10 potential core domains for voting. Voting was conducted at the Annual Meeting of IDEOM on 18 June 2022. Voting members of IDEOM included 23 dermatologists, 1 rheumatologist, 3 dermatologists and rheumatologists, 11 industry partners, 9 patients, 8 patient association representatives and 15 researchers. Core domains meeting 75% consensus threshold included: health-related quality of life (95·35%), extent of depigmentation (93·632%), treatment satisfaction including treatment burden (92·86%), location (83·67%), colour matching (82·69%) and maintenance of pigmentation (76·47%). Two domains met 50% threshold including primary diagnosis/comorbidities (59·62%) and trajectory of disease/stabilization (57·45%) and one domain, itch, failed to reach a consensus (38·46%). Using an approach of inclusion of stakeholders from all walks of life, six core domains reached a consensus for inclusion, two achieved partial consensus but required revision to break down the elements (e.g. primary diagnosis and comorbidities should be separated) and itch failed to achieve inclusion. The group continues to work on its core domains set using a broad range of stakeholders to produce a practical set of domains that are of importance to all stakeholders.